Diagnosing air quality changes in the UK during the COVID-19 lockdown using TROPOMI and GEOS-Chem. (29th April 2021) - Potts, Daniel A; Marais, Eloise A; Boesch, Hartmut; Pope, Richard J; Lee, James; Drysdale, Will; Chipperfield, Martyn P; Kerridge, Brian; Siddans, Richard; Moore, David P; Remedios, John
Abstract: The dramatic and sudden reduction in anthropogenic activity due to lockdown measures in the UK in response to the COVID-19 outbreak has resulted in a concerted effort to estimate local and regional changes in air quality, though changes in underlying emissions remain uncertain. Here we combine satellite observations of tropospheric NO2 from TROPOspheric Monitoring Instrument and the Goddard Earth Observing System (GEOS)-Chem 3D chemical transport model to estimate that NO x emissions declined nationwide by ∼20% during the lockdown (23 March to 31 May 2020). Regionally, these range from 22% to 23% in the western portion of the country to 29% in the southeast and Manchester, and >40% in London. We apply a uniform 20% lockdown period emission reduction to GEOS-Chem anthropogenic emissions over the UK to determine that decline in lockdown emissions led to a national decline in PM2.5 of 1.1 μ g m −3, ranging from 0.6 μ g m −3 in Scotland to 2 μ g m −3 in the southwest. The decline in emissions in cities (>40%) is greater than the national average and causes an increase in ozone of ∼2 ppbv in London and Manchester. The change in ozone and PM2.5 concentrations due to emission reductions alone is about half the total change from 2019 to 2020. This emphasizes the need to account for emissions and other factors, in particular meteorology, in future air pollution abatement strategies and regulatory action.